2018
DOI: 10.1016/j.bbrc.2018.08.102
|View full text |Cite
|
Sign up to set email alerts
|

Fludrocortisone stimulates erythropoietin production in the intercalated cells of the collecting ducts

Abstract: Erythropoietin has been thought to be secreted to plasma soon after the production because of the difficulty of Western blot analysis and immunohistochemistry. We established the new methods of Western blot analysis and immunohistochemistry. Using the new methods, we investigated the effects of aldosterone and fludrocortisone, an analogue of aldosterone on erythropoietin mRNA and protein production by the kidneys. Aldosterone stimulated Epo and HIF2α mRNA expressions in tubule suspensions and microdissected me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(58 citation statements)
references
References 26 publications
4
54
0
Order By: Relevance
“…Mujais and colleagues reported Epo mRNA expression in renal tubules using microdissected nephron segments in cobalt chloride-injected rats [29]. We have previously shown that fludrocortisone stimulated Epo production by the intercalated cells of the collecting ducts [20]. Our immunohistochemistry also showed that kidney interstitial cells respond to severe hypoxia by producing Epo.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Mujais and colleagues reported Epo mRNA expression in renal tubules using microdissected nephron segments in cobalt chloride-injected rats [29]. We have previously shown that fludrocortisone stimulated Epo production by the intercalated cells of the collecting ducts [20]. Our immunohistochemistry also showed that kidney interstitial cells respond to severe hypoxia by producing Epo.…”
Section: Discussionsupporting
confidence: 66%
“…Western blot analysis was performed as described previously [20, 22]. Protein was collected from the renal cortex and liver using CelLytic MT (Sigma-Aldrich, C-3228) plus protease inhibitor (Roche, 05892970001).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations